Euphonie, d'Hector Berlioz: de l'uphonie à l'utopie - Malato, Maria Luísa (2020)
In 1844, Hector Berlioz published a small novel about a future land ruled by musical principles, Euphonia. Remake in 1852, in a different critical context, the novel is the last part of another book, Les Soirées de l'Orchestre. "L'Euphonie" is the last meeting when the theatre was already close « for works » and before the Epilogue of the book. These "works" seems to have a collective intention, since the social order is also a musical harmony. Euphonia and eutopia impose themselves on life, on literature and on music, but they seem voted to dystopia, utopia the representation of a non-place, perhaps the only place capable to recreate the world.